pH Level of Swimming Pool, Athlete Behavior, and Dental Erosion at Swimmer Surabaya - Annysa Almira (JURNAL KESEHATAN LINGKUNGAN, 2019)
Dental erosion potentially occurs in swimmer due to exposure to chlorine substances.The purpose of this research was to analyzed level of pH and behaviors related to incidence of dental erosion in swimmers. This research was analytical research with cross sectional design. The research undertaken in KONI Surabaya swimming pool with 33 samples. The process of data retrieval is done by filling questioner and dental examination by dentist. The variable of research was dental erosion, level of pH, swimming frequency, swimming duration, and time being swimmers. The results showed that the variables that have correlation with the incidence of dental erosion were time being swimmers (p = 0,050) and swimming frequency (p=0,032). Athletes can consume water or vegetable after do swim to reduce the acid levels in mouth because water and vegetable can neutralize the acid. In addition, athletes are advised to visit the dentist to get more benefits associated with dental erosion.